2022
DOI: 10.3390/axioms11120700
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Type-II Lehmann Fréchet Parameters via Progressive Type-II Censoring with Applications

Abstract: A new three-parameter Type-II Lehmann Fréchet distribution (LFD-TII), as a reparameterized version of the Kumaraswamy–Fréchet distribution, is considered. In this study, using progressive Type-II censoring, different estimation methods of the LFD-TII parameters and its lifetime functions, namely, reliability and hazard functions, are considered. In a frequentist setup, both the likelihood and product of the spacing estimators of the considered parameters are obtained utilizing the Newton–Raphson method. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This application provides an analysis of a real data set consisting of 30 successive values of precipitation (in inches) in Minneapolis/St Paul for March. This data collection was reported by Hinkley [40] and reexamined by mq -q q m --- Ghitany et al [41], Elshahhat et al [42], and Alotaibi et al [43]. Each point in the March precipitation data is multiplied by ten for convenience, see table 17.…”
Section: March Precipitation Datamentioning
confidence: 97%
“…This application provides an analysis of a real data set consisting of 30 successive values of precipitation (in inches) in Minneapolis/St Paul for March. This data collection was reported by Hinkley [40] and reexamined by mq -q q m --- Ghitany et al [41], Elshahhat et al [42], and Alotaibi et al [43]. Each point in the March precipitation data is multiplied by ten for convenience, see table 17.…”
Section: March Precipitation Datamentioning
confidence: 97%
“…An engineering application employing a real-life data set reported by Murthy et al [24] is analyzed to demonstrate how approaches suggested may be tailored to real phenomena. In recent time, Elshahhat et al [25] reanalyzed this RME data set for AT-II PCS following weightedexponential distribution. This data set which demonstrates the intervals between failures for thirty pieces of repairable mechanical equipment (RME) is given below: 0:11; 0:30; 0:40; 0:45; 0:59; 0:63; 0:70; 0:71; 0:74; 0:77; 0:94; 1:06; 1:17; 1:23; 1:23; 1:24; 1:43; 1:46; 1:49; 1:74; 1:82; 1:86; 1:97; 2:23; 2:37; 2:46; 2:63; 3:46; 4:36; 4:73:…”
Section: Mechanical Equipment Data Analysismentioning
confidence: 99%
“…An engineering application employing a real-life data set reported by Murthy et al [ 24 ] is analyzed to demonstrate how approaches suggested may be tailored to real phenomena. In recent time, Elshahhat et al [ 25 ] reanalyzed this RME data set for AT-II PCS following weighted-exponential distribution. This data set which demonstrates the intervals between failures for thirty pieces of repairable mechanical equipment (RME) is given below: Before proceeding with the analysis, it is important to determine whether the proposed model adequately fits the data.…”
Section: Mechanical Equipment Data Analysismentioning
confidence: 99%
“…In this part, we analyze real data representing the times 22 ball bearings (BBs) rotated before they stopped after one million rotations; see Table 15. Caroni [30] and Elshahhat et al [31] examined this dataset. To examine the superiority of the CJ model, using the BBs data set, the suggested CJ distribution will be compared to the XL, XG, M, L, and E lifetime models.…”
Section: Ball Bearings Datamentioning
confidence: 99%